Determinants of Employee Absence Differentiation - Striker, Małgorzata; Kusideł, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of this article is to examine the changes in the sickness absence rate in Poland in 2005–2015 (in the period for which statistical data allowing for the calculation of this ratio are available) and, first of all, its territorial differentiation in 2012–2015. The research question has been formulated as follows: what are the factors which determine the changes in the absence rate within time (on the whole country level) and in 16 Polish regions? In accordance with the literature review performed, the analyses have covered health (self‑evaluation of health condition, subjective assessment of conditions and quality of living, the mortality in the event of incidence of certain illnesses) as well as social and economic factors (structure of population according to age and sex, the income of households, subjective assessment of the material situation, poverty level, unemployment rate, employment structure according to NACE classification and structure of population according to the education level) which may affect the changes within time and the regional differentiation of the sickness absence rate.